Diode Laser in the Endoscopic Treatment of Obstructive Airway Disease: Two Years Experience in Istanbul - Dalar, L.; Karasulu, L.; Sökücü, S. N.; Altin, S. (The Thoracic and Cardiovascular Surgeon, 2012)
Aim Laser therapy is a well-known technique which has been safely used for almost thirty years to treat endobronchial obstruction. Nd : YAG and Nd : YAP lasers are commonly used lasers, whose safety and efficacy have been investigated in several large series. Diode laser is a new laser system which has been mainly used in urology, endovascular surgery, ENT, and dermatology. In recent years it has been effectively used in endobronchial treatments.Material and Method In this study, 61 patients who underwent endobronchial treatment with a diode laser in the Interventional Pneumology Unit of our hospital were retrospectively evaluated. Fifty-one patients were male. Mean age was 54.72 ± 13.81 years, and a total of 90 laser applications were given. In 39 cases, palliation of a malign obstruction was achieved while cure was achieved in 19 cases with benign obstruction. No major complication other than minor hemorrhage in 4 cases and temporary hypoxia in 2 cases was observed.Conclusion Diode laser can be used as an effective and safe modality for endobronchial treatment.
Keywords: airway (includes related subject matter); bronchial disease (includes injury, stenosis, tumor, etc.); lung cancer treatment (surgery, medical); laser; diode laser; endobronchial treatment; airway obstruction